Violence as an individual concern: responding to technology-facilitated sexual violence within child and adolescent psychiatry - Rindestig, Frida Carlberg; Gillander Gådin, Katja; Jonsson, Linda; Dennhag, Inga (Frontiers in Psychology, 2025)
Technology-facilitated sexual violence (TFSV) is an emerging concern in child and adolescent mental health. This article presents an analysis of how child and adolescent psychiatric professionals conceptualize the phenomenon of TFSV in relation to their clinical practice with patients exposed to this type of violence. Through Reflexive Thematic Analysis, we constructed the overarching theme: Violence as an Individual Concern. Our findings are analyzed through the lens of psychiatrization—a societal process that extends the influence of psychiatry, making social issues into psychiatric problems. This research provides critical insights into how the medicalization of TFSV may inadvertently individualize this broader societal issue.